Error Performance Analysis of the K-best Viterbi Decoding Algorithm - Yoshikawa, Hideki (2018 International Symposium on Information Theory and Its Applications (ISITA), 2018)
The Viterbi algorithm is widely applied for the decoding of the convolutional codes. But the complexity is increase rapidly in the constraint length. The K-best Viterbi decoding algorithm for the convolutional codes is proposed to reduce its decoding complexity. This is expected to apply for Internet of Things(IoT) devices which are low-scale and low-power hardwares. The author have already shown that the exact bit error performance of Viterbi decoding algorithm for convolutional codes. This analytical technique employs the iterative calculation of probability density function of path metrics. In this paper, the application for error performance analysis for K-best Viterbi decoding algorithm is demonstrated.